Changes in C57BL6 Mouse Hippocampal Transcriptome Induced by Hypergravity Mimic Acute Corticosterone-Induced Stress - Pulga, Alice; Porte, Yves; Morel, Jean-Luc (Frontiers in Molecular Neuroscience, 2016)
Centrifugation is a widely used procedure to study the impact of altered gravity on Earth, as observed during spaceflights, allowing us to understand how a long-term physical constraint can condition the mammalian physiology. It is known that mice, placed in classical cages and maintained during 21 days in a centrifuge at 3G gravity level, undergo physiological adaptations due to hypergravity and/or stress. Indeed, an increase of corticosterone levels has been previously measured in the plasma of 3G-exposed mice. Corticosterone is known to modify neuronal activity during memory processes. Although learning and memory performances cannot be assessed during the centrifugation, literature largely described a large panel of proteins (channels, second messengers, transcription factors, structural proteins) which expressions are modified during memory processing. Thus, we used the Illumina technology to compare the whole hippocampal transcriptome of three groups of C57Bl6/J mice, in order to gain insights into the effects of hypergravity on cerebral functions. Namely, a group of 21 days 3G-centrifuged mice was compared to (1) a group subjected to an acute corticosterone injection, (2) a group receiving a transdermal chronic administration of corticosterone during 21 days and (3) aged mice because aging could be characterized by a decrease of hippocampus functions and memory impairment. Our results suggest that hypergravity stress induced by corticosterone administration and aging modulate the expression of genes in the hippocampus. However, the modulations of the transcriptome observed in these conditions are not identical. Hypergravity affects per se the hippocampus transcriptome and probably modifies its activity. Hypergravity induced changes in hippocampal transcriptome were more similar to acute injection than chronic diffusion of corticosterone or aging.